A framework for training teachers and trainers to use educational multimedia. (1st January 2000) - Valtonen, Kari; Artimaa, Ossi
The article contains a framework for training teachers and trainers to use and produce educational multimedia. The first section describes the background to the need for this kind of a training program. The influence of the changes in working life on today's vocational training and education are discussed here. The background chapter also gives a description of the ongoing changes in trainers' and program designers' work. The second section deals with the basic concepts of training. Terms like Open and Distance Learning (ODL), Computer Aided Learning (CAL), Multimedia and the Internet are discussed. The third section is a description of the target groups of training vocational adult teachers who utilise multimedia technology in their own work. In the Virtual Multimedia Factory project, a similar framework for teachers who also take part in the design and production of educational multimedia was designed and another was developed for training teleworkers. Section four is the actual framework for the training of trainers. General objectives are defined as well as the specific skills, which are achieved after completing the training program. It also contains instructions on how to implement the program and a practical curriculum with detailed descriptions of the modules. The program has been tested in Finland and some Finnish language learning material has been made for it.